Definitions of two species groups of Stenothemus Bourgeois (Coleoptera, Cantharidae), with descriptions of three new species from China - Ge, Shujuan; Yang, Xingke; Liu, Haoyu; Yang, Yuxia (Zootaxa, 2021)
Two new species-groups of the cantharid genus Stenothmeus Bourgeois are defined, S. laterophysus species-group and S. notaticollis species-group. The S. laterophysus species-group is composed of two species, including S. laterophysus Švihla, 2004 and a new species, S. nigritibius Y. Yang et H. Liu, sp. nov., and characterized by the pitch black elytra and bicolored legs, the subrounded pronotum with widely rounded anterior angles and projecting posterior angles, male genitalia with slender ventral processes of parameres which are slightly bent inwards at apical parts, laterophyses tilting ventrally at an angle of more than 45° with dorsal plates, compressed at apical parts, as well as the slender spermathecal duct, extremely long spermatheca and diverticulum. The S. notaticollis species-group consists of five species, including S. notaticollis (Gorham, 1895), S. bourgeoisi Wittmer, 1974, S. tamil Švihla, 2011 and two new species, S. parameratus Y. Yang et S. Ge, sp. nov. and S. acutiapicis Y. Yang et X. Yang, sp. nov., which is differentiated from the S. laterophysus species-group by the more variable body coloration, elytra pitch black or black brown or pale-yellow, male genitalia with thick or flattened ventral processes of parameres which are diverging apically, laterophyses parallel to dorsal plates, expanded at apices, as well as the stout spermathecal duct, moderately long spermatheca and diverticulum. The above species are illustrated with photographs of habitus, male genitalia, abdominal sternites and internal genitalia of female. A key for the identification of these species is provided and a distribution map is presented.